(untitled) (Research, Society and Development, 2021)
Trends in epidemiology and antifungal susceptibility of Candida species in Brazil between 2019–2020 are reported. A total of 22 isolates diagnosed from candidemia episodes were analyzed. Candida species were identified by specie specific primer and/or sequencing of 28S rDNA. Antifungal susceptibility was determined by CLSI method. C. tropicalis accounted for 11 (50%) cases followed by C. albicans (n=5, 22.73%), C. parapsilosis (n=4, 18.19%), Issatchenkia orientalis (n= 1, 4.54%), and Saccharomyces cerevisiae (n= 1, 4.54%). All Candida isolates were susceptible to amphotericin B and micafungin, and one was dose-dependent to anidulafungin. Eight of 20 Candida isolates were resistant to fluconazole and four sensitive doses dependent. Sixteen of 20 Candida isolates were resistant to voriconazole, and one resistant and one sensitive dose-dependent on caspofungin. Besides, the respective MIC50 and MIC90 values ​​were calculated with fluconazole (MIC50 and MIC90 of 4 and 64µg/mL, respectively) and voriconazole (MIC50 and MIC90 of 16µg/mL) showing the lowest potencies. The spread of fluconazole-resistant in one of major concerns, especially to C. tropicalis. The high use of antifungal drug may be a possible cause related to this scenario. Thus, the susceptibility profile test may be used to know the best way to introduce appropriateness empirical antibiotics therapy. Changing trends in incidence and antifungal susceptibility patterns of six Candida species causing candidemia in Kuwait between 2006–2017 are reported. A total of 2075 isolates obtained from 1448 patients were analyzed. Identity of Candida species isolates was determined by phenotypic methods and confirmed by PCR amplification/PCR-sequencing of rDNA and/or MALDI-TOF MS. Antifungal susceptibility was determined by Etest. C. albicans accounted for 539 (37.22%) cases followed by C. parapsilosis (n = 502, 34.67%), C. tropicalis (n = 210, 14.5%), C. glabrata (n = 148, 10.22%), C. krusei (n = 27, 1.81%) and C. dubliniensis (n = 22, 1.5%). The comparative percent distribution of Candida species causing candidemia between 2006–2011 and 2012–2017 was as follows: C. albicans 41.8% and 33.1%, C. parapsilosis complex 32.01% and 37.04%, C. tropicalis 13.59% and 15.31%, and C. glabrata 8.77% and 11.51%, C. krusei 2.0% and 1.7%, and C. dubliniensis 1.75 and 1.3%, respectively. Three of 371 C. albicans isolates during 2006–2011 and five of 363 during 2012–2017 were resistant to fluconazole. Among C. parapsilosis isolates, one of 310 during 2006–2011 and 21 of 446 during 2012–2017 were resistant to this drug. Furthermore, at an epidemiologic cutoff value (ECV) of ≤0.5 μg/ml, 70.1% C. albicans isolates were wild-type for fluconazole during 2006–2011 as compared to 58.1% during 2012–2017. Likewise, at an ECV of ≤2 μg/ml, 98.0% of C. parapsilosis isolates were wild-type during 2006–2011 as compared to 93.4% during 2012–2017. Clonal spread of fluconazole-resistant C. parapsilosis in one major hospital was documented. An 8.8% shift in favor of non-albicans Candida species with concomitant increase in MICs between the two periods preludes emergence of fluconazole-resistant candidemia cases in Kuwait.Changing trends in incidence and antifungal susceptibility patterns of six Candida species causing candidemia in Kuwait between 2006–2017 are reported. A total of 2075 isolates obtained from 1448 patients were analyzed. Identity of Candida species isolates was determined by phenotypic methods and confirmed by PCR amplification/PCR-sequencing of rDNA and/or MALDI-TOF MS. Antifungal susceptibility was determined by Etest. C. albicans accounted for 539 (37.22%) cases followed by C. parapsilosis (n = 502, 34.67%), C. tropicalis (n = 210, 14.5%), C. glabrata (n = 148, 10.22%), C. krusei (n = 27, 1.81%) and C. dubliniensis (n = 22, 1.5%). The comparative percent distribution of Candida species causing candidemia between 2006–2011 and 2012–2017 was as follows: C. albicans 41.8% and 33.1%, C. parapsilosis complex 32.01% and 37.04%, C. tropicalis 13.59% and 15.31%, and C. glabrata 8.77% and 11.51%, C. krusei 2.0% and 1.7%, and C. dubliniensis 1.75 and 1.3%, respectively. Three of 371 C. albicans isolates during 2006–2011 and five of 363 during 2012–2017 were resistant to fluconazole. Among C. parapsilosis isolates, one of 310 during 2006–2011 and 21 of 446 during 2012–2017 were resistant to this drug. Furthermore, at an epidemiologic cutoff value (ECV) of ≤0.5 μg/ml, 70.1% C. albicans isolates were wild-type for fluconazole during 2006–2011 as compared to 58.1% during 2012–2017. Likewise, at an ECV of ≤2 μg/ml, 98.0% of C. parapsilosis isolates were wild-type during 2006–2011 as compared to 93.4% during 2012–2017. Clonal spread of fluconazole-resistant C. parapsilosis in one major hospital was documented. An 8.8% shift in favor of non-albicans Candida species with concomitant increase in MICs between the two periods preludes emergence of fluconazole-resistant candidemia cases in Kuwait.